EFFICIENCY OF USE OF ORGANIC FERTILIZER IN JAPANESE CUCUMBER (CUCUMIS SATIVUS) - Abilia Tesa Putri, Rilvi
The use of organic fertilizers to increase farming has advantages including improving soil properties and accelerating vegetative and generative growth of plants. This study aims to compare several types of organic fertilizers that are able to provide the best results on the growth parameters and yield of Japanese cucumber (Cucumis sativus). The research was conducted at Screen House A3, Bandung Institute of Technology Campus, Jatinangor from 12 November 2019 to 6 March 2020. The study was conducted using a completely randomized design (CRD) consisting of 4 treatments and 6 replications, namely P1 = control (soil), P2 = 3 kg of soil + 1.5 kg of bokashi fertilizer, P3 = 3 kg of soil + 1.5 kg of vermicompost fertilizer and P4 = 3 kg of soil + 1.5 kg of coffee waste fertilizer. The research data were analyzed statistically with the one-way ANOVA test with a confidence level of 95% (p <0.05). If there was a difference, it was analyzed using the LSD test. The results showed that different organic fertilizers had an effect on growth parameters and plant yields, with the best results shown by vermicompost fertilizer treatment with plant height = 240cm, number of leaves = 24 strands, average male flowers = 9 fruit and average female flowers = 2 fruits and the yield parameter of the number of fruits = 14, the average fruit weight = 179 g, the average fruit length = 17 cm and the average fruit diameter = 27 mm. Based on the mass and energy balance analysis, it was found that the addition of vermicompost fertilizer, bokashi and coffee waste fertilizer did not encourage maximum results because the resulting output was smaller than the input due to the unsuitable microclimate environment. Based on the calculation of efficiency, the results show that soil treatment has an efficiency value that is almost the same as the treatment with added organic fertilizers, namely the results of soil efficiency = 0.898, soil + vermicompost = 0.897, soil + bokashi = 0.858 and soil + coffee waste fertilizer = 0.820. Efforts that can be made to increase the efficiency of fertilizer use are adjusting or engineering the optimum microclimate and edaphic environment for the growth of Japanese cucumber plants and adjusting the dosage and composition of fertilizers.